Risk factors for voriconazole-associated hepatotoxicity in patients with liver dysfunction: a retrospective nested case–control study - Ren, Jing; Cai, Xinfeng; Ge, Wei; Guo, Jinlin; Wang, Shan; Wang, Qinhui; Liu, Linna; Yang, Le; Yang, Qi (Frontiers in Pharmacology, 2025)
IntroductionVoriconazole is widely used to prevent and treat invasive aspergillosis. However, its use is restricted by adverse effects, including acute liver injury (ALI). Patients with hepatic insufficiency are often more susceptible to voriconazole-induced liver injury than those with normal hepatic function. The aim of this study was to determine the incidence and risk factors of ALI in patients with mild or moderate liver dysfunction during voriconazole treatment.MethodsThis single-center nested case–control study involved adult patients treated with voriconazole for at least 3 days. The Child–Pugh score is now extensively utilized to assess liver damage. The hepatotoxicity of voriconazole was assessed in patients with mild or moderate hepatic insufficiency (Child–Pugh A or B). ALI cases were matched with controls based on age and Child–Pugh score. Basic characteristics were compared between patients who developed ALI and those who did not by performing univariate and multivariate conditional logistic regression analyses. The optimal cutoff condition was determined using a receiver operating characteristic curve.ResultsA total of 140 patients (ALI: n = 44; control: n = 96) were enrolled. The incidence of voriconazole-induced ALI in patients with mild or moderate liver dysfunction was 30.6%. The univariate analysis revealed trough voriconazole plasma concentration (VPC), voriconazole treatment duration, activated partial thromboplastin time, and intensive care unit admission as variables for the final analysis. Voriconazole-induced ALI was independently associated with trough VPC (odds ratio [OR]: 1.592, p = 0.013) and voriconazole treatment duration (OR: 1.057, p = 0.005). Notably, the optimal cutoff for treatment duration was 10 days and the recommended trough VPC threshold was 3.81 mg/L.ConclusionThe incidence of voriconazole-induced ALI was higher in patients with mild or moderate liver dysfunction than in the general population. Trough VPC and voriconazole treatment duration are two independent risk factors of ALI. Therefore, voriconazole should be administered with caution to these patients. A lower target trough VPC (<3.81 mg/L) is recommended to minimize the risk of ALI in patients with mild-to-moderate liver dysfunction.